6x-3=-7x-133

Simple and best practice solution for 6x-3=-7x-133 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-3=-7x-133 equation:


Simplifying
6x + -3 = -7x + -133

Reorder the terms:
-3 + 6x = -7x + -133

Reorder the terms:
-3 + 6x = -133 + -7x

Solving
-3 + 6x = -133 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-3 + 6x + 7x = -133 + -7x + 7x

Combine like terms: 6x + 7x = 13x
-3 + 13x = -133 + -7x + 7x

Combine like terms: -7x + 7x = 0
-3 + 13x = -133 + 0
-3 + 13x = -133

Add '3' to each side of the equation.
-3 + 3 + 13x = -133 + 3

Combine like terms: -3 + 3 = 0
0 + 13x = -133 + 3
13x = -133 + 3

Combine like terms: -133 + 3 = -130
13x = -130

Divide each side by '13'.
x = -10

Simplifying
x = -10

See similar equations:

| 4-3x+2x=-18+2 | | 6=16-13d | | -140=4x-6(-x+10) | | 5y=-2x-15 | | 10x^2-42x+44=0 | | 5x+13=35+7x | | -1-2x-6x=-65 | | 5x-4=30x+16 | | 6x-4(2-x)=14 | | -17=-2x-2x-5 | | 2=8x-32 | | 4(5x-4)+4=-10 | | -4=3x+7(-x-4) | | 15x+10=8x+38 | | -2x-8=-5x+28 | | 9(2n-1)=(8n+4)+3 | | 2(x-1)=24 | | 93=-6x+3(-2x-13) | | 8x-12+7=-3 | | 3x^2+30x-4=0 | | 4x+11=10x-7 | | z+5=-5 | | 4(3x-5)+x=z | | 11y-12=6y+8 | | 6y+4=2y+20 | | 5xa+7=c+a | | 4(3x-5)+x= | | 10x+5(z-12)=0 | | -3x-10=-2x+4 | | 0.6(j-2)=0.3l | | 20+x=2(20-2x) | | 14-d=45 |

Equations solver categories